PERBANDINGAN PREDIKSI KEBANGKRUTAN MENGGUNAKAN MODEL ALTMAN MODIFIKASI, SPRINGATE, ZMIJEWSKI DAN GROVER PT RATU PRABU ENERGI TBK - Budhi Suparningsih; Ella Siti Chaeriah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study examines comparative analysis to predict bankruptcy using the modified Altman, Springate, Zmijewski and Grover models at PT. Ratu Prabu Energi, Tbk. which is engaged in the mining sector. This study aims to predict bankruptcy at PT. Ratu Prabu Energi, Tbk. and to evaluate whether the predictions match the actual conditions of the company. The type of research applied is a case study at PT. Ratu Prabu Energi, Tbk. during 2009 until 2018. Data were analyzed using qualitative descriptive analysis techniques. The results of the analysis of the four bankruptcy models have different results, although there are some in the position of the Safe Zone but the value is very small and almost close to the Distress Zone, so the company seems to have unfavorable financial conditions as indicated by the low weighting value of the four bankruptcy models . From the beginning this condition has been seen from the ratios represented in each bankruptcy model. Of the four bankruptcy models, this gives a fairly high value deviation in the Altman Z-Score Modification model rather than using the Springate, Zmijewski and Grofer bankruptcy models.